Paul Kolstoe (with a contribution by Andrei Edemsky), Russians in the Former Soviet Republics, London: Hurst Publishers, 1995, 340 s., 35 £; Erik Kulavig, Russisk nationalisme 1986-1992, Odense: Odense Universitetsforlag, 1995,96 s., 100,00kr. - Skak, Mette (Politica, 1995)
-